1977
DOI: 10.1016/0032-0633(77)90090-3
|View full text |Cite
|
Sign up to set email alerts
|

The causes of recurrent geomagnetic storms

Abstract: We studied the causes of recurrent geomagnetic activity by analyzing

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
64
0

Year Published

1978
1978
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(65 citation statements)
references
References 49 publications
(43 reference statements)
1
64
0
Order By: Relevance
“…, 1974. The C9 index, as illustrated by Burlaga and Lepping (1978), showed no discontinuities during this period, justifying the assumption made here that the coronal structures, and by inference interplanetary streams,remained largely unchanged for the whole period of observation.…”
Section: Radial Variation Of Electron Densities and Temperaturessupporting
confidence: 79%
See 1 more Smart Citation
“…, 1974. The C9 index, as illustrated by Burlaga and Lepping (1978), showed no discontinuities during this period, justifying the assumption made here that the coronal structures, and by inference interplanetary streams,remained largely unchanged for the whole period of observation.…”
Section: Radial Variation Of Electron Densities and Temperaturessupporting
confidence: 79%
“…These observations were made continuously during a period of 80 days, or about 2^ solar rotation periods, during which the spacecraft moved from a heliocentric distance of 0.85 to 0.45 AU. There were well-marked repetitive corotating high speed streams and rarefactions during this time, and the characte:istic density variations (Burlaga et al, 1978) were observed. The electron distribution function observed for electrons propagating toward the sun :almost always has a suprathermal (halo) population distinguishable from the thermal (core) population, as has been observed on other satellites in earth orbit for some years (Montgomery et al, 1968).…”
Section: Introductionmentioning
confidence: 78%
“…It is evident however, that the stream fields, though increasing, have continued to be at low levels during the rise of cycle 24, and 4 years into the cycle have barely reached the lowest levels detected since observations began. Geomagnetic activity associated with streams is typically associated with intermittent intervals of southward fields associated with large amplitude Alfvénic fluctuations (e.g., Burlaga & Lepping 1977;Tsurutani et al 2006; and references therein). The weaker fields imply that such southward fields are also likely to be reduced during the rise of cycle 24, resulting in lower levels of geomagnetic activity associated with corotating streams.…”
Section: Geoeffectiveness Of Corotating Streamsmentioning
confidence: 99%
“…It is well known that they play a crucial role in disturbing the space environment as they propagate into the interplanetary medium and interact with the Earth's magnetic field producing strong geomagnetic storms (Allen 1944;Burlaga & Lepping 1977;Gosling et al 1990;Crooker & McAllister 1997;Srivastava & Venkatakrishnan 2002, 2004Srivastava et al 2009). An ability to track a CME through the heliosphere would give a far better estimate of the arrival time, the mass, and the structure of the event as the CME passes over the Earth (Harrison et al 2007).…”
Section: Introductionmentioning
confidence: 99%